Grundlagen mobiler Arbeitsmaschinen - Geimer, MarcusPohlandt, Christian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
The book deals with the topic of mobile machines. In the first part the fundamentals of the machines are treated. The structures and different topologies used in the machines are described in detail. Starting from the energy source, the energy is followed up via engine to the power take-offs. In the second part selected mobile machines from the different areas are presented.